Yearbook 2000. - Sandqvist, Gertrud; Malmö Art Academy, Malmö (Malmö : Malmö Art Academy, 2000)
Gutke, Alexander ; Suneson, Carin ; Jeannin, Lisa ; Ottertun, Magnus ; gran, Edvard ; Fürstenberg, Bettina ; Andersson, Christian ; Thierfelder, Magnus ; Oldeman, Madelene ; Lundstedt, Rikard ; Wessman, Anna ; Carlsson, Camilla ; Berger, Stine ; Grönvall, Jenny ; Bustnes, Maria ; Döggchristensen, Lona ; Andersson, Anna Nordquist ; Holmstrand, Leif ; Jordenö, Sara ; Brunström, Lars ; Hofwander, Fredrik ; Smed, Lotta ; Djurberg, Nathalie ; Josefsson, Sofie ; Olsson, Oskar ; Nygren, Tomas ; Ling, Anna ; Gustavsson, Linn ; Dahlberg, Kajsa ; LSP, Stinus ; Hasselberg, Per ; Blöndal, Karlotta ; Poppelier, Andreas ; Mozard, Tova ; Westerlund, Ylva ; Wikestam, Helena ; Paradis, Hannah ; Andersson, Anna ; Jacobsen, Linnea ; Dahlström, Henrik ; Fransson, Beata ; Scherer, Tomas E. ; Linsh, Carl ; Lokoy, Kay ; Slätis, David ; Bokström, Anna ; Lyngkaer, Ditte
Engels & Zweeds
boek